PENGARUH PAD, DAU, DAK DAN DBH TERHADAP ALOKASI BELANJA DAERAH - Pertiwi, Elisa Rahmawati; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to analyze and to examine the Local Own Source Revenue (PAD), general allocation fund (DAU), special allocation fund (DAK), and Profit Sharing Fund (DBH) to the local expenditure allocation (ABD). The population of this research is all districts / cities in East Java Province, with the numbers of samples are 35 districts / cities.This research has been carried out by using quantitative approach and secondary data in the form of Budget Realization Statement which has been presented in Examination Result Report of The Audit Board of The Republik of Indonesia of districts / cities in East Java Province in 2012-2015 periods. The analysis has been carried out by using multiple linear regressions analysis technique with SPSS 16 application (Statistical Product and Service Solutions).The result of the research which has been carried out by using multiple linear regressions shows that: 1) Local Own Source Revenue gives positive influence to the local expenditure allocation at districts / cities government in East Java province, 2) General allocation fund gives positive influence to the local expenditure allocation at districts / cities government in East Java province, 3) specific allocation fund gives positive influence to the local expenditure allocation at districts / cities government in East Java province, 4) Profit sharing fund gives positive influence to the local expenditure allocation at districts / cities in East Java province. Keywords: Local own source revenue, general allocation fund, specific allocation fund, profit sharing fund, local expenditure.